SEBARAN JENIS TANAH DI SUB DAERAH ALIRAN SUNGAI KARANG MUMUS MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Dwi Agung Pramono (Fakultas Teknik Universitas Lambung Mangkurat, 2016)
The development of Geographic Information System (GIS) in the present can be used to provide information of a physical condition of the region. The information presented varies greatly depending on the purpose of making the GIS, although not 100% perfect, but has been widely used to replace information retrieval through field surveys that take longer and relatively more expensive, so that many people who seek information using Information Systems Geographically, one of them is to find information about the distribution of soil types. The research belongs to field research, and laboratory research and spatial analysis. Field research in question is the process of this research activity to observe the land physically, laboratory research is a research activity conducted by using the process of observation of soil samples taken from the field and then analyzed in the laboratory. Spatial analysis of data through Geographic Information System (GIS) method to give description of soil condition in study area. In terms of variables, the research can be classified type of descriptive research, where researchers take samples to create a picture of the situation or events with no previous treatment. The results of research based on spatial analysts in the study area are land type associations of Tropudults; Dystropepts of 28,673.81 Ha or about 89.5% of the Karang Mumus Watershed area. While the association Tropaquepts; Fluvaquents; Tropohemist is the smallest of 1,261.82 ha or about 3.9% of the Karang Mumus Watershed area, in addition to the Tropudults association; Tropaquepts has an area of 2,115.91 Ha or 6.6%.